The Brand Essence of L’Occitane through Verbal and Visual Expressions in Its Advertisement Videos - Eva Violina (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This thesis aims at revealing the brand essence that is shaped by hidden messages through verbal and visual expressions in L’Occitane’s advertisement videos. In examining the message, Firstly, the writer starts her analysis by finding out the keyword(s) in both of the advertisement videos in finding out the verbal expressions. Then, she proceeds to capture the visual expressions from both of the advertisement videos which support the verbal expressions. In revealing the hidden messages, the writer uses denotation in order to find the literal meaning and connotation in order to reveal the second layer. Based on her analysis, she finds that the brand essence of L’Occitane is “going back to nature”. The brand essence is supported by three hidden messages that each of the hidden message conceives several connotative layers which connect to the brand essence. Key words: Brand essence, denotation and connotation, verbal expressions, visual expressions, natural based product.